REPRESENTASI PEMAHAMAN KONSEP PECAHAN DESIMAL DITINJAU DARI PERBEDAAN GENDER PADA SISWA KELAS IV SEKOLAH DASAR - Hasriana, A.; Bahrullah, Bahrullah; Basri, Muh (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
REPRESENTATION OF UNDERSTANDING THE CONCEPT OF FRACTION ASSESSED FROM GENDER DIFFERENCES IN PRIVATE VOCATIONAL SCHOOL STUDENTS FOR CLASS IVThis research is a qualitative study that aims to describe the representation of the understanding of the concept of decimal fractions for male and female students as well as differences in the representation of understanding the concept of decimal fractions between male students and female students. This study took 9 (nine) informants, consisting of three male students and three female students. Two teachers and one principal. The data collection method uses in-depth interview techniques. observation and documentation. The interview technique was conducted in a structured manner using interview guidelines. The data analysis technique used three components, namely data reduction, data presentation and drawing conclusions. The results of this study indicate that the representation of the conceptual understanding of male students is slow in accepting the material because male students tend to be indifferent and play more. The understanding of the concept of decimal fractions for female students is more improved, because female students pay more attention to the material while studying so that female students understand it more quickly, while the difference is that there is a difference in the level of understanding of male and female students. This difference is due to internal factors, namely self-awareness of understanding how important it is to learn to develop oneself and provision to live life and also external factors, which can be in the form of stimuli from other people, or the surrounding environment that can affect the psychology of the person concerned.